Socialization of covid-19 prevention for children at kaye aceh village, southwest aceh regency, aceh province, indonesia - Sofia Sofia; Meilisa Ariani; Zitkala Sa (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Corona virus disease (COVID-19) is a disease that was first identified in China and has become infectious worldwide. For almost two years, this disease is still an unfinished problem in several areas in Indonesia, including Aceh Province especially in Southwest Aceh Regency. This virus attacks all age groups, including children. Therefore, education about COVID-19 to children is a necessity that must be met. This activity aims to minimize the prevention and control of the COVID-19 virus by providing socialization in order to prevent the spread of COVID-19. The location of this activity was in Kaye Aceh, Southwest Aceh Regency, Aceh Province, Indonesia. The respondents were 40 elementary and junior high school children who lived in this area. The method used in this community services program was learning by doing to the children. The children were given explanations of how to wash hands properly, wear masks, using hand sanitizer, and physical distancing. Results showed that the children understand about COVID-19 and how to break the chain of the spread of COVID-19. It is recommended for children to get used of the good behavior to stop the spread of COVID-19 on their daily life throughout the pandemic.